The Role of Student Parents' Community in School-Based Management in Elementary School - Elis Suryati; Seni Apriliya; Erwin Rahayu Saputra (Universitas Pakuan, 2023)
This study aims to analyze the role of the Parents’ Association (Paguyuban Orang Tua Siswa) in supporting the implementation of School-Based Management (SBM) at the elementary school level. The research adopts a qualitative descriptive approach, focusing on how parental participation contributes to decision-making, resource management, and the enhancement of educational quality. Data were collected through interviews, observations, and document analysis involving school principals, teachers, and active members of the Parents’ Association in several public elementary schools. The findings reveal that the Parents’ Association plays a significant role as a strategic partner in promoting school autonomy by participating in financial transparency, academic supervision, and community empowerment programs. Parents’ involvement encourages stronger collaboration between schools and communities, aligning with the principles of participatory leadership and accountability in SBM. However, challenges such as uneven parental engagement, limited understanding of managerial processes, and socio-economic disparities hinder the effectiveness of their contributions. The study concludes that strengthening communication, leadership support, and capacity-building initiatives for parents is essential to maximize their impact in achieving sustainable, community-driven school management practices.